Navigering i utrygge medielandskap – revurdering af de unges kritiske og produktive mediebruk - Erstad, Ola; Gilje, Øystein (Aktualitet - Litteratur, kultur og medier, 2021)
In this article, we turn our attention to different understandings of two key aspects of media pedagogy - critical media awareness and creative production. Critical media literacy describes young people’s ability to understand media messages and not be uncritical of content they encounter through various channels. Creative media production concerns how young people learn to create themselves through various social media. Drawing on qualitative and quantitative data we explore to what extent and in what ways young people are critical and productive in their approaches to today’s media culture. The findings highlight how children and young people relate to media development as media actors in a complex digital media ecology.